Biomechanical performance of three fiberglass post cementation techniques: Imaging, in vitro, and in silico analysis - Hoshino, Isis Almela Endo [UNESP]; Santos, Paulo Henrique dos [UNESP]; Briso, André Luiz Fraga [UNESP]; Sundfeld, Renato Herman [UNESP]; Yamaguchi, Satoshi; Rocha, Eduardo Passos [UNESP]; Anchieta, Rodolfo Bruniera [UNESP] (Japan Prosthodontic Society, 2023)
Purpose: The structural integrity of the resin cement layer, the bond strength, and the biomechanical behavior of different fiberglass post cementation techniques were evaluated. Methods: Thirty-three bovine incisors were divided into three groups (n = 11): conventional fiberglass post (CFP), conventional fiberglass post in flared root canals (CFL), and relined fiberglass post (RFP). Six specimens from each group were submitted for high-resolution microcomputed tomography (μCT) to evaluate the integrity and presence/volume of voids at the resin cement layer. Finite element analysis (FEA) of two three-dimensional (3D) models of each group were conducted, one considered ideal (without interface defects) and another containing the conditions identified in the μCT analysis. Push-out bond strength tests were conducted for all specimens. Results: The CFL group had the greatest mean values of void (Thirds cervical: 73.67; middle: 95.67; apical: 47.33) and gap concentration (Thirds cervical: 14.67; middle: 15.83; apical: 8.33) compared with CFP and RFP. A significant difference in bond strength was observed between the cervical (1.33 MPa) and middle thirds (1.85 MPa) compared with the apical third (4.85 MPa) of the CFL. A significant difference was observed in the bond strength in the CFL (1.33 MPa) and RFP (3.29 MPa) in the cervical third, which were statistically similar to the bond strength of the CFP. The tensile stress distributions were similar in most structures, localized in the cervical region on the lingual surface. Conclusions: Structural defects in the interface layer might influence the bond strength and biomechanical behavior under the different fiberglass post cementations.
Keywords: Cementation; Fiberglass post; Finite element analysis; Micro CT; Porosity